Analysis of a Rotating Disk System with Axial Cooling Air. (25th July 2017) - Jiao, Z.; Fu, S.; Kawakubo, T.; Ohuchida, S.; Tamaki, H.
Abstract : In this article, a series of simulations of a rotating disk system with air cooling is introduced. These simulations are performed with the realizable k-ε eddy-viscosity model. Computational results illustrate the effect of the cooling air and disk rotation on the temperature of the disk surface. The maximum rotating disk speed reaches about 78300 rpm and the range of Reynolds numbers based on rotation speed is from about 0.7 × 10 6 to 3 × 10 6 . The present work shows that the flow structure in the gap, which is on the opposite side of the cooling air, is rather similar to different cooling air flows. The temperature goes up as the rotating speed increases. The temperature in this gap will first decrease when the cooling air increases under lower mass flow rate. But when the cooling air continues to increase, the temperature will rise up indicating the existence of an optimum value of the cooling flow rate.